Benturan Kepentingan Transaksi Tertentu di Pasar Modal - Siti Anisah (Jurnal Hukum IUS QUIA IUSTUM, 2004)
To avoid the interest conflict on certain transaction, the major agreement of independent share hoider must be put into in action. The reaiity, many kinds of disobeying on the agreement are found. The law enforcement by Money Market Supervisor as the highest authority in the Money Market has not been maximal and it tends to be unjust to the parties on certain transactional conflict.